2022
DOI: 10.1177/00224871221105813
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Mixed Methods Study of Norwegian Preservice Teachers’ Beliefs About Sources of Teaching Knowledge and Motivation to Learn From Theory and Practice

Abstract: We set out to investigate preservice teachers’ beliefs about sources of teaching knowledge and their motivation to learn from practice and theory in teacher education in a longitudinal study ( n = 96, at the beginning of the study). Participants placed more trust in experiential knowledge sources compared with formalized sources and participants’ beliefs about sources of teaching knowledge generally predicted their motivation to learn from different sources. Quantitative results were further supported and elab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…Our findings align with prior research (Fives and Buehl, 2008;Bråten and Ferguson, 2015;Ferguson et al, 2022) but also provide new insight by merit of participants' responses to scenarios and their reasoning about the described problems. In particular, the pre-service teachers' beliefs about student 10.3389/feduc.2022.975105 performance actually placed most emphasis on the role of the teacher, their actions, and the ways they interact with students and adapt and vary their teaching methods and exercises.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our findings align with prior research (Fives and Buehl, 2008;Bråten and Ferguson, 2015;Ferguson et al, 2022) but also provide new insight by merit of participants' responses to scenarios and their reasoning about the described problems. In particular, the pre-service teachers' beliefs about student 10.3389/feduc.2022.975105 performance actually placed most emphasis on the role of the teacher, their actions, and the ways they interact with students and adapt and vary their teaching methods and exercises.…”
Section: Discussionsupporting
confidence: 89%
“…The authors identified the following six main themes related to sources of teaching knowledge in participants' responses: formal education in terms of pre-service education and professional development; formalized bodies of knowledge, including research articles and the Internet; observational (or vicarious) learning from other teachers; collaboration and shared meaning making; enactive experiences from personal, professional, and other experiences; and self-reflection and synthesis of information and experiences. In accordance with this study, pre-service teachers' and teachers' emphasis on personal, enactive, and experienced-based knowledge has been confirmed in later work (e.g., Bråten and Ferguson, 2015;Kiemer and Kollar, 2021;Thomm et al, 2021c;Ferguson et al, 2022). Still, the mechanisms explaining this emphasis have only recently become the object of more systematic investigation.…”
Section: Teacher Beliefs About Sources Of Teaching Knowledgesupporting
confidence: 80%
See 3 more Smart Citations